Evaluación de dosis de ácido húmico granulado de leonardita y ácidos húmicos y fúlvicos con macro y micro elementos en el cultivo de col china (Brassica pekinensis) Variedad Kiboho 90 F-1, bajo condiciones agroecológicas en el Distrito de Lamas. - Ponce Ramírez, Danny Graviel (2016)
Chinese cabbage (Brassica pekinensis), is native to the Far East, is cultivated in China for many years . It is a vegetable that begins gradually spread to every continent and in recent years has been widespread in Europe. Brassica pekinensis , required to develop a pH between 6.5 and 7, are neither good nor overly acidic or very alkaline soils. They thrive in climates where minimum temperatures are 15 ° C and maximum 20 ° C. In the San Martin region, promoting the cultivation of Chinese cabbage, it is having limitations on the growth and development of leaves, due to the lack of incorporation of nutrients to the soil and climatic variability factors. Such as temperature, wind and solar radiation, which effect results in the decreased production. This study aimed to evaluate the effect of 3 different doses humic acid granules Leonardite and humic and fulvic acids with macro and micro nutrients on yield and crop productivity of Chinese cabbage (Brassica pekinensis) Variety Kiboho 90 F- 1 under normal conditions Lamas. The work was developed on the premises of Fundo the Pacific, located in the district of Lamas, Province of Lamas, San Martin region, at a height of 835 m.s.n.m. in an area of tropical dry forest (bs - T) of Peru's high jungle. For the development of this work , the statistical block design was used completely random ( DBCA ) with three blocks, five treatments making a total of 15 experimental units. Whose treatments were T0 (control), T1 (100 Kg / ha of humic acid), T2 (200 Kg / ha of humic acid), T3 (30 L / Ha humic and fulvic acids with macro and micro nutrients), T4 (50 Lt. / Ha humic and fulvic acids with macro and micro nutrients ). From the results it can be concluded that the T4 (50 kg / ha- 1 AH and F.) with an average of 132,456.87 kg / ha -1 performance was statistically equal to T3 (30 kg / ha AH 1 and F), who earned an average yield of 127,598.56 kg / ha -1. Q4 exceeded statistically treatments T2 (200 Kg / ha -1 AH), T1 (100 Kg / ha -1 AH) and T0 (Witness) who reached averages of 120,625.81 kg / ha -1, 117649.19 kg / ha -1 113,810.67 kg / ha -1 respectively. These results were similar behavior to that obtained in the diameter and weight of the strips, which were linear positive. As for peel weight averages obtained from the application of liquid humic acid (4.65 kg) determined an increase of 9.66 % over the average of treatments with humic acid granules (4.24) and 13.97 % over the witness treatment (4.08 kg). These being proportional to the diameter of peeled logs. Likewise, T4 treatment (50 kg / ha - 1 AH and F.), was showed better effect in the production, so it is regarded as the proper dosage for a better yield in the cultivation of Chinese cabbage (Brassica pekinensis) Variety Kiboho 90 F- 1 under agroecological conditions of Lamas. In all treatments behaved economically profitable, they threw indices B / C reater than 1, with the T3 (30 Lt / ha-1) treatment which achieved better results compared with other treatments with 1.85 and Percentage of des profitability 181.74 %. While it is true that the application of humic acids granular and liquid, increased crop yield and net profit, profitability was affected by the costs of humic acids and granulated most strongly by the liquid humic acid